Spatial and temporal biomarkers responses of Astyanax jacuhiensis (Cope, 1894)(Characiformes: Characidae) from the middle rio Uruguai, Brazil - Loro,Vania Lucia (2015)
Due to intense agricultural activity in the rio Uruguai (South Brazil), there is the potential for aquatic contamination by agrochemicals. In this region, there are many reservoirs to meet the water demand for rice fields, forming lentic environments. In line with this information, the aim of this study was to show a comparative analysis of some biomarkers, such as lipid peroxidation (TBARS), gluthatione S-transferase (GST), non-protein thiols (NPSH), amino acids (AA) and piscine micronucleus tests (MNE) in Astyanax jacuhiensis from lentic and lotic environments in the middle rio Uruguai region, comparing warm and cold seasons. Eight pesticides were found in water samples, with propoxur having the highest concentration found in both environments and seasons. Fish from the warm season showed higher levels of biochemical biomarkers, and fish from the cold season showed higher levels of MNE and AA. TBARS and AA presented higher levels in fish from the river, while GST, NPSH, MNE and AA presented higher levels in fish from dams. These environments have different characteristics in terms of redox potential, aeration, sedimentation, trophic structure, agrochemicals input and others, which may affect the physiological and biochemical responses of fish in against adverse situations.